A comprehensive review for power production and economic feasibility on hybrid energy systems for remote communities. Issue 1 (31st December 2022) - Edwin, M.; Nair, M. Saranya; Joseph Sekhar, S.
Abstract : In the past few years, a lot of research has taken place in the selection, design and modelling of the hybrid renewable energy systems. Scaled down hybrid energy systems gain popularity around the world as a feasible approach for eco-friendly environment, shrinking energy cost and constancy of flourishing power supply. Hybrid energy systems are erected in several remote locations where renewable energy resources are abundant. A well-designed hybrid energy system can be cost effective and reliable besides improves the quality of life in remote areas. Therefore, the study on hybrid energy system has become one of the key research areas to provide a way for the rapid growth of renewable energy system, denationalise electric power markets and responsive demand. The relevant areas related to the implementation of renewable energy, such as combinations of energy sources, potential economic factors and effective usage of software tools are discussed in this paper.